2008
DOI: 10.1183/09031936.00058507
|View full text |Cite
|
Sign up to set email alerts
|

Lung carcinomas with a basaloid pattern: a study of 90 cases focusing on their poor prognosis

Abstract: Lung carcinoma with a basaloid pattern (BC) is classified as either a basaloid variant of squamous cell carcinoma (SCC) or as variant of large cell carcinoma (LCC) depending on the presence of a squamous component. In a previous study of 37 cases, the present authors showed that BC presented with a shorter median and overall survival.In order to confirm its clinical significance in a larger series, 90 BC, including 46 basaloid variants of LCC and 44 basaloid variants of SCC, were compared with 1,328 other nons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
54
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 25 publications
3
54
3
Order By: Relevance
“…Without stratification for SSEA-4, the relapse rate (42%) and 5-yr survival rate (62%) of the entire collective was similar to that reported for overall early-stage NSCLC or poorly differentiated SCC (PDSC) [1][2][3][4][5][6]. This is in contrast to the results of Brambilla and co-workers [1,5,6], who reported a significantly worse outcome of basaloid carcinomas as compared with other NSCLC or PDSC: While the latter displayed a 5-yr survival rate of 44% and 47-55% in stage I/II disease, respectively, the 5-yr survival rate of early-stage basaloid NSCLC was 10-27% [1,5,6]. Conversely, previous studies of KIM et al [2] and WANG et al [28] in two Asian collectives likewise demonstrated comparable relapse rates (33-55%) and 5-yr survival rate (50-57%) for…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…Without stratification for SSEA-4, the relapse rate (42%) and 5-yr survival rate (62%) of the entire collective was similar to that reported for overall early-stage NSCLC or poorly differentiated SCC (PDSC) [1][2][3][4][5][6]. This is in contrast to the results of Brambilla and co-workers [1,5,6], who reported a significantly worse outcome of basaloid carcinomas as compared with other NSCLC or PDSC: While the latter displayed a 5-yr survival rate of 44% and 47-55% in stage I/II disease, respectively, the 5-yr survival rate of early-stage basaloid NSCLC was 10-27% [1,5,6]. Conversely, previous studies of KIM et al [2] and WANG et al [28] in two Asian collectives likewise demonstrated comparable relapse rates (33-55%) and 5-yr survival rate (50-57%) for…”
Section: Discussionsupporting
confidence: 51%
“…Basaloid lung cancer represents a rare variant of NSCLC and showed an unfavourable prognosis in a number of studies [1,5,6]. BRAMBILLA et al [5], who were the first to describe this variant, speculated as early as 1992 that basaloid NSCLC might derive from a pluri-or multipotent pulmonary stem cell.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Basaloid carcinoma account for about 5% of non-small cell lung carcinomas (NSCLC) and were identified as a histopathologic entity with a dismal prognosis (9,10). Among NSCLC and lung squamous cell carcinomas, the basaloid carcinoma (pure type) and the squamous variant of basaloid carcinoma (mixed basaloid SCC; WHO 2004) show the poorest prognosis (11). In the absence of specific molecular characteristics, basaloid carcinomas, in their pure form, were presented as a subtype of large-cell carcinoma (WHO 2004), while they very likely present distinct biologic characteristics, whose definition would be helpful in diagnosis and in the design of targeted treatment.…”
Section: Introductionmentioning
confidence: 99%